Smartphones, the new addiction: Causes and Consequences for Elementary and High School Students According to Teachers and Experts. Issue 2 (3rd April 2023) - Rodríguez-Torrico, Paula; San-Martín, Sonia; Jiménez, Nadia
Abstract: A major concern is how to tackle student smartphone addiction (SSA). First, however, analysis of the definition, causes, and consequences of SSA is necessary. There is a lack of consensus in this regard, and little research considers its multidisciplinary nature. This article first reviews the key literature across different disciplines. Based on this review, a conceptual model of SSA, its causes, and its consequences is proposed. Qualitative analysis is then used to explore this model empirically for the case of elementary and high school students. A total of 90 articles were reviewed. In addition, 33 in-depth interviews with experts and teachers from four European countries were conducted. The literature review shows the multifaceted nature of SSA. According to the literature, SSA is the result of biological, psychological, social, and technological factors and leads to health, performance, and social problems. The qualitative analysis identifies specific areas to develop this proposed conceptual model, based on the views of experts and teachers in relation to SSA.